OCCURRENCE OF POWDERY MILDEW CAUSED BY Podosphaera sp. ON INVASIVE WEED Ageratum houstonianum IN NEPAL - Hari Sharan Adhikari; Lal Bahadur Thapa; Sanjay Kumar Jha (SEAMEO BIOTROP, 2026)
ARTICLE HIGHLIGHTS- First report of Podosphaera sp. on invasive Ageratum houstonianum in Nepal.- Pathogen identified by unique cask-shaped conidia, chasmothecia and fibrosin bodies.- Potential biocontrol agent discovered for managing this invasive weed.- This weed can act as a pathogen reservoir; monitoring is essential to protect nearby crops.ABSTRACTAgeratum houstonianum is an invasive annual weed in Nepal that grows in diverse habitats such as fallow areas, crop fields, and roadsides. This study reported a powdery mildew disease on this weed species, which causal agent was identified as Podosphaera sp. Pathogen identification was based on symptomatology and micromorphological observations. The pathogen was characterized by slightly dark, branched and septate hyphae with nipple-like appressoria; straight and unbranched conidiophore; hyaline and cask-shaped conidia with fibrosin-like bodies. Immature chasmothecia with mycelium-like appendages were also observed. The asci were ellipsoidal with a thin oculus. Based on the literature, the fungus was first reported in Nepal on Ageratum houstonianum. This report expands the known geographical distribution and host range of this powdery mildew pathogen in South Asia and highlights the pathogen as a potential biocontrol agent for this invasive weed. Additionally, A. houstonianum is common in agroecosystem, thus, it can serve as a reservoir of Podosphaera sp. facilitating spread to crop plants. Therefore, careful utilization, monitoring, and management of the pathogen are essential both to control the host weed and to limit the spread of pathogen to crops.